2020
DOI: 10.1038/s41420-020-00337-4
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of p53 mutant as an approach for treatment Her2-positive cancer

Abstract: Breast cancer is one of the world’s leading causes of oncological disease-related death. It is characterized by a high degree of heterogeneity on the clinical, morphological, and molecular levels. Based on molecular profiling breast carcinomas are divided into several subtypes depending on the expression of a number of cell surface receptors, e.g., ER, PR, and HER2. The Her2-positive subtype occurs in ~10–15% of all cases of breast cancer, and is characterized by a worse prognosis of patient survival. This is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 95 publications
1
29
3
Order By: Relevance
“…A study using cancer cell lines with introduced gain-of-function TP53 mutations found an increase in HER2 mRNA expression levels as well as HER2 protein levels [ 28 ]. Analysis of the publicly available breast cancer dataset (GSE22358) confirm significantly higher HER2 mRNA levels in p53 mutant samples ( p = 0.046) compared to p53 wildtype samples [ 29 ]. Mechanistically, mutant p53 has shown to be associated with enhanced transcriptional activity of HSF1 (heat shock transcription factor 1) that targets chaperon Hsp90 which in turn stabilizes the HER2 and p53 proteins, thereby further reinforcing oncogenic signaling [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study using cancer cell lines with introduced gain-of-function TP53 mutations found an increase in HER2 mRNA expression levels as well as HER2 protein levels [ 28 ]. Analysis of the publicly available breast cancer dataset (GSE22358) confirm significantly higher HER2 mRNA levels in p53 mutant samples ( p = 0.046) compared to p53 wildtype samples [ 29 ]. Mechanistically, mutant p53 has shown to be associated with enhanced transcriptional activity of HSF1 (heat shock transcription factor 1) that targets chaperon Hsp90 which in turn stabilizes the HER2 and p53 proteins, thereby further reinforcing oncogenic signaling [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Typically occurring as missense mutations (over 80% of the cases), they involve the DNA binding domain either in DNA contact residues or in residues that have important implication for the conformational structure of p53 [1][2][3][4]; thus, p53 missense mutations generally result in generation of p53 mutant proteins. Evidence from genetically engineered mouse models indicates that the presence of p53 mutant forms facilitates development of more aggressive and metastatic tumours compared to those arising in p53 −\− mice [5][6][7][8][9][10]. Moreover, mouse models with inactivatable p53 hotspot mutation demonstrated that tumours depend on sustained mutant p53 expression [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…This is strongly supported by recent studies showing that heterozygous Rlip deficiency suppresses Her2-driven murine breast cancer (the MMTV-ERBB2 mouse model) as well [31]. The specific protein complexes and their molecular functions remain to be elucidated, but breast tumors from MMTV-ERBB2 mice frequently have mutations in p53, a phenomenon that is also prevalent in human HER2-positive breast cancers [32,33]. In summary, Rlip depletion causes broad transcriptomic and methylomic changes, which could result from a number of effects including altered levels or functions of transcription factors, DNA methylation enzymes, or other regulatory/signaling protein complexes, as well as a generalized shift in the intracellular physiological milieu due to the sustained oxidative or genotoxic stresses of 4-HNE accumulation.…”
Section: Introductionmentioning
confidence: 75%